Losing a Job and (Dis)incentives to Move - Terhi Maczulskij; Petri Böckerman (The Research Institute of the Finnish Economy (ETLA), 2020)
We examine the economic determinants of interregional mobility. Using plant closures and mass lay-offs for identification, we show that there are obstacles in the labor market that prevent a more efficient reallocation of unemployed individuals and jobs. We find that displacement increases the migration probability by ~80 percent. Displaced workers mostly make migration decisions based on economic (dis)incentives, i.e., higher expected wages and lower expected housing prices outside the origin home location increase the probability of moving after a job loss. In contrast, proximity to family, home ownership and poorly functioning housing markets constitute severe constraints for migration. This outcome is concerning for employment prospects, as, among displaced workers, migration is positively linked to a strong attachment to the labor market.
Keywords: J31; J61; J63; 330; Displacement; Internal migration; Housing markets; Expected income; Social capital; Labor market outcomes